Support Pacific neighbours by strengthening indigenous food systems - Mohammed, Essam Yassin (Lowy Institute, 2022)
Across the island states of the Pacific, indigenous food systems have been shaped and refined over centuries to make the most of bountiful natural resources without exhausting them. The exchange of fish and crops is the heartbeat of the Melanesian food system and is deeply embedded in the history, culture, and identity of its people. However, this unique legacy of knowledge has been usurped by centuries of colonialism followed by incorporation, on unequal terms of trade, into the modern, industrialised global food system. Diets – and the food production and distribution systems that supply them – have been supplanted by the influx of imported and processed foods, leaving islands particularly vulnerable to global challenges, from the climate crisis or soaring inflation to food price hikes and public health concerns. But building on the foundations of traditional food practices offers a credible and sustainable pathway to modern island food systems that achieves better health outcomes, climate change resilience, and greater stability across the region.